2012
DOI: 10.1097/coc.0b013e31821d4906
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Oncology Web-based Resources in Spanish-speaking Internet Users

Abstract: Objectives: There currently are few web-based resources written in Spanish providing oncology-specific information. This study examines utilization of Spanish-language oncology web-based resources and evaluates oncology-related Internet browsing practices of Spanish-speaking patients. Methods: OncoLink (http://www.oncolink.org) is the oldest and among the largest Internet-based cancer information resources. In 9/2005, OncoLink pioneered OncoLink en español (OEE) (http://es.oncolink.org), a Spanish translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
3
0
2
Order By: Relevance
“…Given these differences in health information seeking, further research is needed to better understand how information seeking patterns can influence health care use, quality of care, and ultimately health outcomes. When available, culturally and linguistically competent websites that provide disease-specific health information for immigrant populations have been well utilized (Simone et al 2012; Londra et al 2014; Liu, Haukoos, and Sasson 2014; Wang and Yu 2014). However, understanding how these resources strengthen quality of care and service utilization requires additional investigation, particularly when considering the culture and context of health information seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Given these differences in health information seeking, further research is needed to better understand how information seeking patterns can influence health care use, quality of care, and ultimately health outcomes. When available, culturally and linguistically competent websites that provide disease-specific health information for immigrant populations have been well utilized (Simone et al 2012; Londra et al 2014; Liu, Haukoos, and Sasson 2014; Wang and Yu 2014). However, understanding how these resources strengthen quality of care and service utilization requires additional investigation, particularly when considering the culture and context of health information seeking.…”
Section: Discussionmentioning
confidence: 99%
“…These generally relate to inflammatory processes that occur in the penis and include human papilloma virus infection, phimosis, lichen sclerosis and poor penile hygiene . Limited available web resources in Spanish and Portuguese contribute to disparities in information access and disease outcomes . A study of both English‐ and Spanish‐speaking internet users found that penile cancer was the fifth most commonly searched cancer in Spanish, whereas it was not in the top 10 cancers searched in English .…”
Section: Discussionmentioning
confidence: 99%
“…Limited available web resources in Spanish and Portuguese contribute to disparities in information access and disease outcomes . A study of both English‐ and Spanish‐speaking internet users found that penile cancer was the fifth most commonly searched cancer in Spanish, whereas it was not in the top 10 cancers searched in English . By recognizing the differences in both search patterns and web resources available, the content of web‐based oncology resources can be developed to best target the needs of populations at higher risk of penile cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Das Internet hat sich längst als wichtige Informationsquelle für Krebspatienten bei der Suche nach Informationen über Krebserkrankung und -versorgung etabliert [1][2][3]. Einigen Studien zufolge nutzen 41 % [1] bis 63 % [4] dieser Patientenpopulation das Internet, um nach erkrankungsrelevanten Informationen zu suchen, wobei diese Zahl je nach Krebsart variieren kann [1,5].…”
Section: Introductionunclassified
“…Einigen Studien zufolge nutzen 41 % [1] bis 63 % [4] dieser Patientenpopulation das Internet, um nach erkrankungsrelevanten Informationen zu suchen, wobei diese Zahl je nach Krebsart variieren kann [1,5]. Dieses Verhalten ist verschiedenen Gründen zuzuschreiben: Einerseits brauchen manche Patienten besonders viele Informationen, um mit ihrer Erkrankung umgehen zu können [2,4,5], andererseits greifen Patienten auf Internetrecherchen zurück, da sie unzufrieden mit den Informationen sind, die die Ärzte mit ihnen teilen [6]. Ferner wird häufig die Suche nach sozialer Unterstützung genannt [7].…”
Section: Introductionunclassified